1994
DOI: 10.1073/pnas.91.15.7370
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of the gene encoding 2,3-oxidosqualene-lanosterol cyclase from Saccharomyces cerevisiae.

Abstract: TheERG7geneencodingoxidosqualene-lans-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
55
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 41 publications
1
55
0
Order By: Relevance
“…It was assumed that the aromatic rings of the conserved tryptophan residues of this motif could stabilize the intermediary carbocations (72,102). This would be in agreement with other models of active centers with carbocation intermediates (21,41,88). However, the SHC structure revealed that all QW motifs are located at the C terminus of an exposed ␣-helix, with the eponymous part of the motif (Q-X 3 -G-X-W) generating the loop structure (see Fig.…”
Section: Structure-function Relationships Of Shcsmentioning
confidence: 50%
“…It was assumed that the aromatic rings of the conserved tryptophan residues of this motif could stabilize the intermediary carbocations (72,102). This would be in agreement with other models of active centers with carbocation intermediates (21,41,88). However, the SHC structure revealed that all QW motifs are located at the C terminus of an exposed ␣-helix, with the eponymous part of the motif (Q-X 3 -G-X-W) generating the loop structure (see Fig.…”
Section: Structure-function Relationships Of Shcsmentioning
confidence: 50%
“…2,3-Oxidosqualene cyclase or lanosterol synthase, the product of the ERG7 gene, performs several ring closures and bond cleavages in this very complex reaction. 50 The ERG7 gene from yeast has been cloned by two laboratories 50,237 which should allow for characterization of this gene and the encoded enzyme. The pathway has now reached the point where a sterol molecule is present and the question to be asked from here to the end of the pathway is whether the intermediate produced at each step is able to meet both the bulk and sparking requirements and thus permit growth.…”
Section: Sterol Biosynthesis In Yeast: Farnesyl Pyrophosphate To Ergomentioning
confidence: 99%
“…According to the PEPPLOT program (36), a typical QW motif contains part of a (3-strand at the N terminus and a turn at the C terminus. We (37) and others (16) have postulated that the aromatic amino acids of the QW motif might play a structural or functional role in catalysis by stabilizing the carbocationic intermediates through cation-I interactions.…”
mentioning
confidence: 99%
“…Recently, two OSC enzymes have been cloned and sequenced from the fungi Saccharomyces cerevisiae (15,16) and Candida albicans (17)(18)(19)). An oxidosqualene cycloartenol-cyclase was cloned and sequenced from the plantArabidopsis thaliana (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation